A systematic review of brief respiratory, embodiment, cognitive, and mindfulness interventions to reduce state anxiety - Chin, Phoebe; Gorman, Faye; Beck, Fraser; Russell, Bruce R.; Stephan, Klaas E.; Harrison, Olivia K. (Frontiers in Psychology, 2024)
Anxiety is one of the most prevalent mental health conditions worldwide, and psychotherapeutic techniques can be employed to help manage and mitigate symptoms. While the available therapies are numerous, key strategies often involve cognitive and/or embodiment techniques. Within bodycentered methods, breathing-oriented approaches are particularly prevalent, using either attention towards or active control of breathing. As the perception of body states (i.e., interoception) is thought to be an integral component of emotion generation, these embodiment and breathing techniques may be key in addressing the miscommunication between the brain and body that is thought to exist with anxiety. As such, we conducted a systematic review and meta-analysis to assess the effects of acute administration of psychological interventions for state anxiety. We considered interventions that focused on cognitive, embodiment or breathing strategies, or a combination of these techniques. Our systematic review was conducted in accordance with the PRISMA statement and registered prospectively in PROSPERO. A literature search for randomized controlled trials was conducted in PubMed, PsycINFO, and Scopus. Twelve studies met our inclusion criteria, and study characteristics, quality and effect sizes were assessed. A single cognitive study was found to produce a moderate reduction in state anxiety, while moderate to large effects were found across studies assessing embodiment practices. In contrast, studies which utilized breathing-based interventions alone produced inconsistent results, with both attention towards and active control of breathing producing large to no effects depending on the technique employed. Finally, consistent moderate effects were found with combination techniques that involved passive attention (e.g. towards cognitions, body and/or breathing), with active combination techniques producing inconsistent results. Therefore, while study numbers are limited regarding brief interventions, cognitive and embodiment techniques are consistently helpful for reducing state anxiety, while breathing-based exercises need to consider the specific technique employed, and how successful this may be for each individual. Furthermore, combined practices such as mindfulness can also be successful, although care must be taken when introducing an active change to one or more elements.